The physical profile of adult male basketball players: Differences between competitive levels and playing positions - Ferioli, D.; Rampinini, E.; Bosio, A.; La Torre, A.; Azzolini, M.; Coutts, A. J. (Journal of Sports Sciences, 2018)
This study examined the physical differences in adult male basketball players of different competitive level and playing position using a large cohort. In the middle of the regular season, 129 players from four different Divisions completed a Yo-YoIR1 and, after 3-to-8 days, they performed a 6-min continuous running test (Mognoni`s test), a counter-movement jump (CMJ) test and a 5-min High-intensity Intermittent running test (HIT). Magnitude-based inferences revealed that differences in HIT were very likely moderate between Division I and II and likely small between Division II and III. The differences in absolute peak power and force produced during CMJs between Division I and II and between Division II and III were possibly small. Differences in Yo-YoIR1 and Mognoni`s test were very likely-to-almost certain moderate/large between Division III and VI. We observed possibly-to-likely small differences in HIT and Mognoni`s test between guards and forwards and almost certainly moderate differences in absolute peak power and force during CMJs between guards and centres. The ability to sustain high-intensity intermittent efforts (i.e. HIT) and strength/power characteristics can differentiate between competitive level, while strength/power characteristics discriminate guards from forwards/centres. These findings inform practitioners on the development of identification programs and training activities in basketball.